Integrated Antenatal Care At Public Health Care - Mitha Permata Dini; Sesotiyaningsih Madiyaning Utami; Ratna Dwi Wulandari (Universitas Aisyah Pringsewu, 2023)
Integrated antenatal services are comprehensive and quality antenatal services provided to all pregnant women; in which they are integrated with other programs that require intervention during pregnancy. This study aimed to analyze the integrated antenatal care team of Public Health Care (Puskesmas) in the Sidoarjo Regency using the Input-Process-Output approach. This study was observational and descriptive with a cross-sectional research design. Data collection was done using a questionnaire and checklist. This study used a total population of 26 Public Health Care Integrated Antenatal Care Teams. The data collected were analyzed using descriptive analysis. The results show that there is a tendency in the team input which do not affect the process, and there are tendencies in the process which affect the output. Suggestions that can be done to improve cohesion are by placing the service rooms closely, conducting training on leadership/interprofessional practice/conflict management, giving rewards to team members who perform well, and reviewing the existing policies. Abstrak: Pelayanan antenatal terpadu adalah pelayanan antenatal komprehensif dan berkualitas yang diberikan kepada semua ibu hamil, terpadu dengan program lain yang memerlukan intervensi selama kehamilan. Tujuan penelitian ini adalah menganalisis tim pelayanan antenatal terpadu Puskesmas di Kabupaten Sidoarjo dengan pendekatan Input-Process-Output. Jenis penelitian ini merupakan penelitian deskriptif observasional dengan design penelitian cross sectional. Pengumpulan data menggunakan kuesioner dan checklist. Penelitian ini menggunakan total populasi sejumlah 26 tim pelayanan antenatal terpadu Puskesmas. Data penelitian dengan menggunakan analisis deskriptif. Hasil penelitian menunjukkan pada input, tim terdapat kecenderungan tidak mempengaruhi proses dan pada proses terdapat kecenderungan mempengaruhi output. Untuk meningkatkan cohesion dengan mendekatkan ruang pelayanan, pelatihan, leadership/interprofesional practice/manajemen conflict, reward bagi anggota tim yang berkinerja baik serta policy review kebijakan yang ada.